Complexities of core-periphery relation: An analysis of the late Raúl Prebisch - Natália Bracarense (Duke University, Center for the History of Political Economy (CHOPE), 2016)
The work of Raúl Prebisch is typically summarized by two of his important contributions to development economics: the center-periphery paradigm together with his diagnosis of Latin America's development struggles. Recent investigations have, however, shed light on the nature of Prebisch's early work, especially his understanding of business cycles (Sember 2010; Perez and Vernengo 2012). Although the present paper focuses on his center and periphery, it examines Prebisch's later work, casting a different light on his most enduring contribution to the field. While early in his career, Prebisch held a standard structuralist position by the 1960s, Prebisch embraced a less rigid understanding of the relationship between center and periphery, adding multiple layers to his analysis of the latter.
Keywords: B2; B4; O1; 330; Development Economic Theory; Latin American Structuralism; History of Economic Thought; Raúl Prebisch